Geographic Variation and Determinants of Help Seeking Behaviour Among Married Women Subjected to Intimate Partner Violence Evidence from National Population Survey - Muluneh, Muluken Dessalegn; Alemu, Yeshemebet Worku; Meazaw4, Maereg Wagnew (Springer Nature, 2021)
Background: Help seeking behaviour amongst married women who experienced Intimate Partner Violence (IPV) has received limited attention in Africa. This study examines the geographic variation and investigates determinants of help seeking behaviour amongst married women in Ethiopia. Methods: This study analysed data from the 2016 Ethiopian Demographic and Health Survey (EDHS). Data was extracted for married women age 15–49 years old who experienced IPV. Factors associated with help seeking behaviour were identified using multiple logistic regression adjusted for clustering and weighing. The weighted proportion of factors associated with help seeking behaviour was exported to ArcGIS to conduct autocorrelation analysis. Results: The prevalence of help seeking behaviour among married women who experienced IPV was 19.8% (95% CI: 15.9–24.3%). Only 9.2% of them sought help from a formal source (such as police, lawyer or doctor). Multiple logistic regression analyses showed physical violence (Adjusted odds ratio (AOR)=2.76), educational attainment (AOR=2.1), a partner’s alcohol consumption (AOR=1.9), partner’s controlling behaviour (AOR= 2.4), partner’s employment status, (AOR= 1.9) and wealth index (AOR=2.8) were significantly associated factors with help seeking behaviour among married women who experienced IPV in Ethiopia (P< 0.05). Women in Benishangul-Gumuz, Gambella, Harari, Western and Eastern Amhara, and Afar had the lowest odds of help seeking behaviour (P< 0.001) after experiencing IPV. Conclusion: The findings of this study suggest that poor help seeking behaviour for married women experiencing IPV is a significant public health problem in Ethiopia. Multiple interrelated factors were associated with poor help seeking behaviour. These factors include women’s level of educational attainment, women experiencing physical violence, partners exhibiting controlling behaviour, partner’s alcohol consumption, the employment status of the partner, and wealth status of the household were important predictors of help seeking behaviour. Policies and interventions need to be tailored to address these factors to improve women’s health outcomes and to prevent IPV.
© The Author(s). 2021 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article's Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated in a credit line to the data.
Keywords: Intimate partner violence; Married women; Geographic; Hierarchical logistic; DHS, Ethiopia